DEFORMATION-ENHANCED METAMORPHIC REACTIONS AND THE RHEOLOGY OF HIGH-PRESSURE SHEAR ZONES, WESTERN GNEISS REGION, NORWAY - Terry M.P.; Heidelbach F. (My University, 2006)
Microstructural and petrological analysis of samples with increasing strain in high-pressure (HP) shear zones from the Haram garnet corona gabbro give insights into the deformation mechanisms of minerals, rheological properties of the shear zone and the role of deformation in enhancing metamorphic reactions. Scanning electron microscopy with electron backscattering diffraction (SEM-EBSD), compositional mapping and petrographic analysis were used to evaluate the nature of deformation in both reactants and products associated with eclogitization. Plagioclase with a shape-preferred orientation that occurs in the interior part of layers in the mylonitic sample deformed by intracrystalline glide on the (0 0 1)[1 0 0] slip system. In omphacite, crystallographic preferred orientations indicate slip on (1 0 0)[0 0 1] and (1 1 0)[0 0 1] during deformation. Fine-grained garnet deformed by diffusion creep and grain-boundary sliding. Ilmenite deformed by dislocation glide on the basal and, at higher strains, prism planes in the a direction. Relationships among the minerals present and petrological analysis indicate that deformation and metamorphism in the shear zones began at 500-650 °C and 0.5-1.4 GPa and continued during prograde metamorphism to ultra-high-pressure (UHP) conditions. Both products and reactants show evidence of syn- and post-kinematic growth indicating that prograde reactions continued after strain was partitioned away. The restriction of post-kinematic growth to narrow regions at the interface of garnet and plagioclase and preservation of earlier syn-kinematic microstructures in older parts layers that were involved in reactions during deformation show that diffusion distances were significantly shortened when strain was partitioned away, demonstrating that deformation played an important role in enhancing metamorphic reactions. Two important consequences of deformation observed in these shear zones are: (i) the homogenization of chemical composition gradients occurred by mixing and grain-boundary migration and (ii) composition changes in zoned metamorphic garnet by lengthening diffusion distances. The application of experimental flow laws to the main phases present in nearly monomineralic layers yield upper limits for stresses of 100-150 MPa and lower limits for strain rates of 10-12 to 10-13 s-1 as deformation conditions for the shear zones in the Haram gabbro that were produced during subduction of the Baltica craton and resulted in the production of HP and UHP metamorphic rocks. © 2005 Blackwell Publishing Ltd.
Keywords: ECLOGITE; GARNET; HIGH-PRESSURE METAMORPHISM; ILMENITE; NORWAY; OMPHACITE; PLAGIOCLASE; RHEOLOGY; SHEAR ZONE; STRAIN RATE; SUBDUCTION; WESTERN GNEISS REGION